Geology of a Transpressional Orogen Developed During Ridge-Trench Interaction Along the North Pacific Margin 2003
DOI: 10.1130/0-8137-2371-x.19
|View full text |Cite
|
Sign up to set email alerts
|

Geologic signature of early Tertiary ridge subduction in Alaska

Abstract: A mid-Paleocene to early Eocene encounter between an oceanic spreading center and a subduction zone produced a wide range of geologic features in Alaska. The most striking effects are seen in the accretionary prism (Chugach-Prince William terrane), where 61 to 50 Ma near-trench granitic to gabbroic plutons were intruded into accreted trench sediments that had been deposited only a few million years earlier. This short time interval also saw the genesis of ophiolites, some of which contain syngenetic massive su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 105 publications
(196 reference statements)
2
86
0
Order By: Relevance
“…Being located in a similar zonal cross-strike position in the orogen, it is possible that this may have originated from the same spreading ridge-subduction zone interaction as for the Lawrence Head event, as a diachronous event that depended on particular features and orientations of the spreading ridge and trench geometries. The example of the well-constrained evidence for early Tertiary ridge subduction at the Alaska Trench (Bradley et al 2003) is instructive for comparison to these northern Appalachian relicts of the variable geological effects caused by ridge subduction including both the scale and the relative timing of such an event along a subduction system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being located in a similar zonal cross-strike position in the orogen, it is possible that this may have originated from the same spreading ridge-subduction zone interaction as for the Lawrence Head event, as a diachronous event that depended on particular features and orientations of the spreading ridge and trench geometries. The example of the well-constrained evidence for early Tertiary ridge subduction at the Alaska Trench (Bradley et al 2003) is instructive for comparison to these northern Appalachian relicts of the variable geological effects caused by ridge subduction including both the scale and the relative timing of such an event along a subduction system.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for uplift of the fore-arc as the ridge enters the trench is seen in Alaska and Chile in the form of significant vertical and horizontal block motions, and brittle and ductile faulting in the fore-arc (Bradley et al 2003;Lagabrielle et al 2000), and in the case of Alaska, a change from trench-parallel flow directions in trench sediments to variable flow directions (Bradley et al 2003). In Newfoundland, uplift is indicated by the Cheneyville conglomerate containing porphyry cobbles unconformably overlying the Dunnage Mélange, local shallow marine limestone overlying the Lawrence Head Volcanics (and equivalent upper Summerford Group volcanic rocks); the regionally extensive red argillite and chert elsewhere found above the Lawrence Head may perhaps indicate sub-aerial erosion of the arc platform.…”
Section: Comparison Of Newfoundland With Known Ridge Subduction Systemsmentioning
confidence: 99%
“…It along with a KULA-RESUR? (Resurrection, Farallon or another unknown plate) spreading ridge and corresponding plate to the E subducted together under Alaska [13,14]. It has been assumed they subducted completely into the mantle as the oceanic remaining part of the KULA-RESUR?…”
Section: David Publishingmentioning
confidence: 99%
“…In the Prince William Sound (PWS, Fig. 2), 38 Ma near trench plutons formed [14] due to a PAC-KULA ridge slab window. These plutons were then shut off underneath by the oblique NNW flat-slab subducting PAC from the S. The subducted KULA-RESUR?…”
Section: David Publishingmentioning
confidence: 99%
“…The restudies confirmed that, compared with cratonic North America (Kent and Irving 2010), paleomagnetic inclinations imply ~3000 km of northward displacement since 70 Ma, placing the Carmacks Group at the latitude of San Francisco during its eruption. It was presumably translated northward as part of the Kula plate before the latter's disappearance into the eastern Aleutian Trench ~50 Ma (DeLong et al 1978;Bradley et al 1993). Most Cordilleran geologists still reject the Baja BC hypothesis because they cannot find structures capable of accommodating large (>1000 km) displacements of the requisite age (Price and Carmichael 1986).…”
mentioning
confidence: 99%